2016
DOI: 10.1039/c6dt03907c
|View full text |Cite
|
Sign up to set email alerts
|

Calcium complexation and acid–base properties ofl-gulonate, a diastereomer ofd-gluconate

Abstract: The Ca(ii)-complexation and acid-base properties of l-gulonic acid (HGul), a diastereomer of d-gluconic acid (HGluc) differing only in the configurations of C2 and C5 have been investigated viaH and C NMR spectroscopies, Ca-ISE- and pH-potentiometry, polarimetry and freezing point depression. Data obtained for Gul/HGul have been compared with those of Gluc/HGluc. It was found that some properties (acid dissociation constant, the stoichiometry and formation constants of the Ca(ii)-complexes) were insensitive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…The free ion concentrations thus grant valuable insight into the ionresponsive behavior of the systems. 4,5 The free ion concentrations can be measured using electrochemical probes [5][6][7] or fluorescent dyes. [8][9][10] However, such measurements can be expensive and inconvenient to perform in addition to NMR, particularly when only limited quantities of sample are available.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The free ion concentrations thus grant valuable insight into the ionresponsive behavior of the systems. 4,5 The free ion concentrations can be measured using electrochemical probes [5][6][7] or fluorescent dyes. [8][9][10] However, such measurements can be expensive and inconvenient to perform in addition to NMR, particularly when only limited quantities of sample are available.…”
mentioning
confidence: 99%
“…When complexing species are present, the concentration of free ions can be very different to the total concentrations of Ca or Mg. The free ion concentrations thus grant valuable insight into the ion-responsive behavior of the systems. , The free ion concentrations can be measured using electrochemical probes or fluorescent dyes. However, such measurements can be expensive and inconvenient to perform in addition to NMR, particularly when only limited quantities of sample are available. Furthermore, the insertion of electrodes can cause serious damage to soft-solid samples such as gels while electrochemical methods are also wholly unsuited to study the internal ion gradients that can occur in these systems. , Methods for the direct measurement of free Ca 2+ and Mg 2+ concentrations by NMR are thus required.…”
mentioning
confidence: 99%
“…As expected, the structure of the titration curves greatly resembled to those of D-gluconate due to the structural similarity of the two ligands: heptagluconate only differs from gluconate in an additional -CH 2 -OH group and thus the same speciation model could be envisaged (Figure 12). Upon fitting the potentiometric data, it was found that assuming the formation of CaHpgl Nevertheless, these results are in line with those reported for heptagluconate [66] and gulonate [142] in I = 1 M (NaCl) medium.…”
Section: Complexation Of Ca 2+ By Heptagluconate Ions In Alkaline Mediumsupporting
confidence: 87%